Mapping of Integrated Local Wisdom to Develop Instructional Material - Supiatman, Lis; Aryni, Yen; Sari, Putri Lidiana Permata; Siahaan, Micael Olivan; Nasution, Ravli Akbar; Sari, Devi Manda (Journal of English Language and Education, 2023)
Asahan Regency is regency consisting of various local wisdom. The substances of local wisdom can be integrated in learning activities, one of them in the course of writing, especially writing genres. However, based on empirical studies obtained the integration of local wisdom, especially in the subject of writing has not been done by the lecturers. To perform such integration, it is necessary to do the mapping of local wisdom which is expected to become the basis of the development of instructional writing materials. The research used a library research. The researcher carried out the process of collecting data in the form of books in the Library, Archives and Documentation Offices. After the data collection, content analysis technique was used to comprehend the data. Then, the researcher analyzed data by studying the data in the books through inductive data and deductive data. The research found some local wisdom that can be formed in some genres. They are in the form of customs, ritual, traditional knowledge, art, and cultural heritage. The content of local wisdom in Asahan Regency can be mapped and preserved so that the results can be used as the basis of the development of instructional writing materials.